Responses to Compound Objects in Monkey Inferotemporal Cortex: The Whole Is Equal to the Sum of the Discrete Parts - Sripati, Arun P. (Society for Neuroscience, 2010)
It is commonly thought that neurons in monkey inferotemporal cortex are conjunction selective—that a neuron will respond to an image if and only if it contains a required combination of parts. However, this view is based on the results of experiments manipulating closely adjacent or confluent parts. Neurons may have been sensitive not to the conjunction of parts as such but to the presence of a unique feature created where they abut. Here, we compare responses to two sets of images, one composed of spatially separate and the other of abutting parts. We show that the influences of spatially separate parts combine, to a very close approximation, according to a linear rule. Nonlinearities are more prominent—although still weak—in responses to images composed of abutting parts.